Monkeypox transmission following exposure in healthcare facilities in nonendemic settings: Low risk but limited literature. (9th July 2022) - Zachary, Kimon C.; Shenoy, Erica S.
Abstract: Transmission risk of monkeypox in healthcare settings outside endemic regions has not been well defined. A rapid review of the literature, including cases outside monkeypox-endemic regions from 2000 to 2022 identified a single reported case of transmission. Available literature is limited by nonstandardized exposure definitions and limited detail describing exposures.